Pengaruh Fraud Diamond Terhadap Kecurangan Laporan Keuangan - Dita Nuur Frida Sari (2021)
This research is quantitative study that aims to find out the impact of fraud diamond for financial statement fraud. Diamond fraud theory are measured by Pressure (external pressure and financial target), Opportunity (nature of industry), Rationalization (total accrual), and Capability (Political Connection). The method used is purposive sampling. The sample consisted of 47 data companies from 64 data companies from building construction, real estate and property sector listed on the Indonesian Stock Exchange and multiple regression linear analysis with some help of programming data using STATA v.16. The result of this research showed that nature of industry and political connection has significant positive effect, external pressure and rationalization have significant negative effect while financial target has no significant effect to financial statement fraud Keywords: external pressure; financial target; nature of industry; rationalization and political connection